Peran Penyuluh Pertanian dalam Ketersediaan Bibit Sapi di Kabupaten Muna Sulawesi Tenggara - Hidayat Hidayat; La Ode Muhammad Munadi; La Ode Sahaba (Fakultas Pertanian Universitas Halu Oleo, 2021)
Livestock is an agricultural sector that has a great opportunity to be developed. The research was conducted in October to December 2020 aimed to find out the role of agricultural extensionists in the availability of beef cattle seedlings in Muna Regency. The study using survey method with the determination of research samples determined deliberately (Purposive) connects research variables in the form of human resource availability and public perception of beef cattle development with the number of respondents 150 people. The results showed that the Availability of Human Resources (HR) Muna Regency for PKB 3 people, PPL 37 people and IB officers 30 people, while for public perception the availability of Bali cow seedlings as much as 32.85% said available, 50.35% quite available, and not available 16.8%.